New potential functions for passivity based sliding mode control. Issue 1 (2023) - Sakata, N.; Fujimoto, K.; Maruta, I.
Abstract: Recently, passivity-based sliding mode control has been proposed for mechanical port-Hamiltonian systems. This controller has properties of both sliding mode control and passivity-based control, and Lyapunov stability is ensured by a Hamiltonian function with a non-smooth potential function. In the authors' previous study, a special form of non-smooth potential function is considered and there are few parameters to adjust the controller for various control objectives. This paper proposes a new passivity-based sliding mode controller based on a wider class of potential functions. This approach enables us to reduce chattering and improve the behavior in reaching mode by adjusting parameters. The effectiveness of the proposed method is demonstrated by a numerical simulation.